Creative Writing Learning Model Development Strategy Based on Information and Communication Technology (ICT) - Prasetyo Yuli Kurniawan; Subyantoro Subyantoro; Ida Zulaeha; Tommi Yuniawan (Universitas Negeri Semarang, 2023)
This research aims to determine the development strategy of a creative writing learning model based on information and communication technology (ICT). This study is a literature review research along with relevant secondary data. The data is derived from sources such as books and research articles published in national and international journals. The research procedure uses Mary W. George's theory. This study concludes that in developing a creative writing learning model based on information and communication technology (ICT), the strategy used by Utomo (2020) can be utilized to produce a prototype of a creative writing learning model. The learning model is developed based on five components, namely (1) syntax, (2) social system, (3) reaction principle, (4) support system, and (5) instructional impact. In addition, the strategy for developing a creative writing learning model can also be integrated with information and communication technology (ICT) to achieve learning goals in the digital era.